ANALISIS FINANSIAL KUD MANDIRI MOJOPAHIT JAYA DESA SARI GALUH KECAMATAN TAPUNG RAYA KABUPATEN KAMPAR - Yusmini '; Didi Muwardi; Ade Indragunawan (Indonesian Journal of Agricultural Economics, 2011)
This reseacrh is aimed to analyze the financial and performance growth of cooperativeMandiri Mojopahit Jaya during last three years. This research was carried out atcooperative Mandiri Mojopahit Jaya village Sari Galuh District of East Tapung RayaKampar Regence. The method used was case study in order to see the monetary ratio ofcooperative Mandiri Mojopahit Jaya. Interview was also done with active member ofcooperative Mandiri Mojopahit Jaya totally 30 members. The sample was takes byClaster Random Sampling. Based of financial criteria the research result show that coopMojopahit Jaya is in liquid position, laverge ratio indicate that cooperative MandiriMojopahit Jaya is solvable. Active ratio shown that cooperative Mandiri Mojopahit Jayastill depend on capital. From rentability ratio cooperative is still lower compared withthe using of total grand capital.Key words: financial, monetary ratio, the growth of KUD